In‐cytoplasm mitochondrial transplantation for mesenchymal stem cells engineering and tissue regeneration - Xudong Yao; Yuanzhu Ma; Wenyan Zhou; Youguo Liao; Zongsheng Jiang; Junxin Lin; Qiulin He; Hongwei Wu; Wei Wei; Xiaozhao Wang; Mikael Björklund; Hongwei Ouyang (Wiley, 2022)
Abstract Stem cell therapies are unsatisfactory due to poor cell survival and engraftment. Stem cell used for therapy must be properly "tuned" for a harsh in vivo environment. Herein, we report that transfer of exogenous mitochondria (mito) to adipose‐derived mesenchymal stem cells (ADSCs) can effectively boost their energy levels, enabling efficient cell engraftment. Importantly, the entire process of exogeneous mitochondrial endocytosis is captured by high‐content live‐cell imaging. Mitochondrial transfer leads to acutely enhanced bioenergetics, with nearly 17% of higher adenosine 5'‐triphosphate (ATP) levels in ADSCs treated with high mitochondrial dosage and further results in altered secretome profiles of ADSCs. Mitochondrial transfer also induced the expression of 334 mRNAs in ADSCs, which are mainly linked to signaling pathways associated with DNA replication and cell division. We hypothesize that increase in ATP and cyclin‐dependent kinase 1 and 2 expression might be responsible for promoting enhanced proliferation, migration, and differentiation of ADSCs in vitro. More importantly, mito‐transferred ADSCs display prolonged cell survival, engraftment and horizontal transfer of exogenous mitochondria to surrounding cells in a full‐thickness skin defect rat model with improved skin repair compared with nontreated ADSCs. These results demonstrate that intracellular mitochondrial transplantation is a promising strategy to engineer stem cells for tissue regeneration.